Penerapan Hukum Islam dalam Praktik Jual Beli oleh Anak di Bawah Umur di Masyarakat Kontemporer - Zakir, Muhammad; Khairi, Rifqil; Rahmawati, Rahmawati; Assyifa, Zubaidah (Journal of Legal Sustainability, 2025)
The practice of buying and selling by minors is a growing phenomenon in contemporary society, both in simple transactions in the local community and through digital media. This situation raises legal issues related to the validity of contracts and child protection from an Islamic legal perspective. This study aims to analyze the application of Islamic law to the practice of buying and selling by minors in the context of contemporary society. This study uses a juridical-normative method with a qualitative approach through library research. Data sources include the Qur'an, Hadith, classical and contemporary fiqh books, scientific journals, and relevant laws and regulations. Data were analyzed using a descriptive-analytical method with a maqasid al-shariah approach. The results show that Islamic law essentially permits the involvement of minors in buying and selling practices on a limited basis, provided they have the permission and supervision of a guardian and do not cause harm. Meanwhile, buying and selling by minors who are not yet mumayyiz is considered invalid. In the context of contemporary society, the application of Islamic law must be contextualized, emphasizing the principle of protecting children's minds and property. This research confirms that Islamic law plays a role not only as a legal norm but also as an ethical guideline for protecting and guiding children in safe and beneficial economic activities.